Effect of metal doping in Bi2WO6 micro-flowers for enhanced photoelectrochemical water splitting. Issue 23 (1st December 2022) - Bera, Susmita; Samajdar, Soumita; Pal, Sourabh; Das, Pradip Sekhar; Jones, Leanne A.H.; Finch, Harry; Dhanak, Vinod R.; Ghosh, Srabanti
Abstract: Design and fabrication of artificial catalytic systems to mimic natural photosynthesis which can harvest solar energy and directly convert into useable or storable energy resources may resolve the global energy crisis. Remarkably, photocatalysis is an efficient approach to utilize solar photons in order to drive the thermodynamic uphill reaction to generate chemical fuels in presence of efficient photocatalyst. Bismuth tungsten oxide (Bi2 WO6 ) is a typical Aurivillius double perovskite oxides and has received an increasing research interest for water splitting due to moderate bandgap, superior chemical and thermal stability. However, the solar light absorption of bare Bi2 WO6 is not significant in visible region, and low charge separation efficiency limits the photocatalytic performance. In the present work, in situ doping of flower like Bi2 WO6 microstructure (∼6–8 μm) by metal (Mo, Fe, Zn) may improve the absorption and charge transfer efficiency. The metal doping effectively reduces the bandgap of Bi2 WO6 which in turn enhances light absorption in the visible region. Notably, photoelectrochemical water splitting highly improved after metal doping, for example, Mo doping showed highest photocurrent density which is fifty-seven times higher than bare Bi2 WO6 . The band structure of Bi2 WO6 before and after doping has been investigated on the basis of valence band XPS and Mott-Schottky analysis to understand the effect of doping in optoelectronic properties. The enhanced activity may originate due to presence of additional electronic states via doping, lower ionization potential, work function energy and enhanced number of charge carriers at the electrode-electrolyte interface during water splitting.